Menunjukan Sikap Etis dalam Pembelajaran di Sekolah Dasar - Novita Anggraeni; Elvina Rahmah; Febrianti Dwi Putri; Tiara Alifa Mumtahanah (INDO PUBLISHING, 2026)
This study aims to analyze the role of teachers’ ethical attitudes in shaping discipline and character among elementary school students. Using a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and document studies involving teachers, students, principals, and parents. The findings reveal that teachers’ ethical behavior significantly influences students’ discipline through moral modeling, empathetic relationships, and fair classroom management. Teachers serve as moral figures whose integrity, responsibility, and fairness are reflected in every classroom decision and interaction. Integrating ethical values into the learning process fosters a positive classroom climate built on respect and cooperation, encouraging self-discipline and moral awareness among students. Thus, teachers’ ethical conduct not only reinforces formal discipline but also nurtures students’ character development grounded in integrity and empathy.